2020
DOI: 10.3390/md18090460
|View full text |Cite
|
Sign up to set email alerts
|

Marine Fungus Aspergillus chevalieri TM2-S6 Extract Protects Skin Fibroblasts from Oxidative Stress

Abstract: The strain Aspergillus chevalieri TM2-S6 was isolated from the sponge Axinella and identified according to internal transcribed spacer (ITS) molecular sequence homology with Aspergillus species from the section Restricti. The strain was cultivated 9 days on potato dextrose broth (PDB), and the medium evaluated as antioxidant on primary normal human dermal fibroblasts (NHDF). The cultivation broth was submitted to sterile filtration, lyophilized and used without any further processing to give the Aspergillus ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 56 publications
0
15
0
Order By: Relevance
“…RNA isolation, cDNA synthesis, as well as RT-qPCR method analysis were carried out as previously outlined [17][18][19]. Briefly, for RNA isolation (500 ng), the Nucleospin RNA kit (Macherey-Nagel, Germany) was used, and for cDNA (reaction volume of 20 µL), the SuperScript™ First-Strand Synthesis kit (Invitrogen, UK) was used.…”
Section: Rt-qpcr Gene Expression Analysismentioning
confidence: 99%
“…RNA isolation, cDNA synthesis, as well as RT-qPCR method analysis were carried out as previously outlined [17][18][19]. Briefly, for RNA isolation (500 ng), the Nucleospin RNA kit (Macherey-Nagel, Germany) was used, and for cDNA (reaction volume of 20 µL), the SuperScript™ First-Strand Synthesis kit (Invitrogen, UK) was used.…”
Section: Rt-qpcr Gene Expression Analysismentioning
confidence: 99%
“…The anti-oxidant and anti-aging properties of the culture filtrate (ACCB) obtained from the sponge-associated Aspergillus chavalieri TM2-S6 (Tel Aviv-Jaffa, Israeli Mediterranean coast) were also tested on primary normal human dermal fibroblasts (NHDF) through bioassays and molecular approaches [ 115 ]. Chemical analyses on the ACCB ethyl acetate extract revealed two abundant compounds, named Tetrahydroauroglaucin and Flavoglaucin.…”
Section: Sponge Symbionts In Cosmeceutical Fieldmentioning
confidence: 99%
“…Interestingly, the mRNA levels of sirtuin 1 ( SIRT1 ) and sirtuin 2 ( SIRT2 ), implicated in skin aging, were also found up-regulated in H 2 O 2 -induced NHDF cells. Combining these results, the authors concluded that ACCB stimulated cell proliferation, anti-oxidant response and extracellular matrix organization as well as reduced aging, thus proposing ACCB as a perfect candidate for the formulation of cosmetic products [ 115 ].…”
Section: Sponge Symbionts In Cosmeceutical Fieldmentioning
confidence: 99%
“…Since the first report in 1934 of FG and DAG from the terrestrial fungus Aspergillus glaucus [ 7 ], this growing class of C7 alkylated salicylaldehyde derivatives [ 8 ] has been described to possess a broad spectrum of biological activities: antioxidant and radical scavenging properties [ 9 , 10 , 11 ], antimicrobial, antibiofilm [ 12 ], and antifouling activities [ 3 ], anti-inflammatory [ 13 , 14 ] and skin-protective properties under oxidative stress condition [ 15 ] as well as binding affinity to human opioid or cannabinoid receptors [ 16 ].…”
Section: Introductionmentioning
confidence: 99%